THE EFFECT OF INCLUSION IN PINEAPPLE JUICE (Ananas comosus)ON THE QUALITY OF BLOOD (Anadara granosa)DURING COLD STORAGE - Marhan, Ari; Suparmi, Suparmi; Desmelati, Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTBlood clams are a common type of shellfish for the community, its general use is as a consumption material. Blood clams have a fast rotten nature and experience deterioration in quality, so they only last up to 1-2 days. The high water content in blood clams causes blood clams to decompose faster than fish. The purpose of this study was to determine the effect of soaking pineapple juice on the quality of blood clams during storage. This research method is an experimental method, namely soaking blood clam meat in pineapple juice with different concentrations with 45 minutes of soaking time, and as a group is storage time with time intervals of 0, 1, 3 and 5 days. The experimental design used was a non-factorial randomized block design (RAK) consisting of four treatment levels, namely N0 (without pineapple juice), N1 (80% pineapple juice), N2 (90% pineapple juice), Npineapple juice).3 (100%pineapple juice), then pH test, TVB test, TMA and total bacterial colony (TPC) analysis. Furthermore, proximate analysis was carried out such as water, protein and fat content. The results of the study of immersion in pineapple on blood clam meat significantly affected the quality of mussel meat based on the pH value, TVB-N value, TMA, total plate number, protein content, water content and fat content. The best treatment was found in the Ntreatment3 (the addition of 100% pineapple juice) with an average pH value of 5.07, TVB-N value 25.46 mg/100g, TMA value 10.77 mg/100g, total plate number 5 ,4 x 105colonies/g for 3 days storage. The results of the proximate analysis were the value of protein content of 10.65%, water 79.83% and fat 0.74%.  Keywords: Blood clams, Cold storage, Pineapple juice.